Caracterização fenotípica, mapeamento de QTL e análise de expressão de genes-candidatos de resistência de trigo a Magnaporthe oryzae - Ferreira, Jéssica Rosset (2019)
The infection of the head by Magnaporthe oryzae is the most dangerous form of wheat blast. The disease is found in Brazil, Bolivia Paraguay, Argentina, Bangladesh and India. The genetic resistance is the best control method of wheat blast. Many studies have been performed to identify wheat resistant genotypes and resistance genes to M. oryzae and to elucidate the mechanism involved in the M. oryzae-wheat interaction. The present work had as general aim to characterize the genetic resistance of wheat to M. oryzae. The specific aims were i) to identify the most efficient variables in the discrimination of genotypes; ii) to evaluate the presence of 2NS/2AS translocation in contrasting genotypes; iii) to identify resistance QTL to M. oryzae at the adult plant stage; and iv) to characterize resistance candidate genes in TILLING mutants and in RNAseq analyses. The severity of bleached spikletes, area under the disease progress curve and proportion of the average grain weight of the inoculated spike in relation to the controls were efficient in the classification of wheat genotypes. These variables should be considered for the characterization of the wheat in response to M. oryzae. Wheat blast resistant lacking the 2NS/2AS translocation were identified. This reinforces the need for studies aiming at the discovery of other genes and/or QTL involved in the resistance. Twelve QTL related to resistance and two with grain production were identified. As far as is known, this is the first QTL mapping of wheat conferring resistance to M. oryzae in the world. No change in the phenotype of wheat TILLING mutants was observed for HSP60 and WIR1b genes. The mutants for Caffeic Acid O-Methyltransferase presented alterations in the reaction to M. oryzae, in seedling and in adult plant stage. Sequencing of wheat head transcriptomes in response to inoculation revealed the molecular functions of heme binding, iron ion binding and oxidoreductase activity as the most representative in GO terms. Exclusively in the resistant genotype CBFusarium ENT014, 24 defense related genes were identified as differentially expressed. These studies allowed the identification of important variables for the characterization of the reaction of wheat genotypes to M. oryzae, resistance QTL and differentially expressed genes.